THE RELATIONSHIP BETWEEN WORKING PERIOD OF BATIK CRAFTSMEN AND INCIDENT OF CARPAL TUNNEL SYNDROME - Subandi, Subandi; Mirawati, Diah Kurnia; Putra, Stefanus Erdana; Hafizhan, Muhammad; Susilo, Wahyu Agung; Danuaji, Rivan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Carpal Tunnel Syndrome (CTS) is the most common mono-neuropathy caused by median nerve entrapment on the wrist. Major risk factor of the CTS is repetitive use of the hand, whether from occupational activities or hobbies. One of the most frequent occupation affected with CTS is the batik craftsmen.Objective: To investigate the relationship between working period of batik craftsmen with the incident of CTS at Kampung Batik Tulis Laweyan.Methods: Participants of this cross-sectional study were 30 batik craftsmen from Kampung Batik Tulis Laweyan who met the inclusion and exclusion criteria. They were classified into two groups based on working period (less or more than five years), clinically examined, and underwent the Nerve Conduction Velocity studies. Bland's classification was administered for grouping the nerve injury. Spearman correlation test was performed to investigate the correlation between working period and incident of CTS.Results: There was a significant medium positive correlation between working period and nerve injury based on Bland’s classification (r=0.559; p=0.013). While the chief complaints were also correlated with the working period, the association was not statistically significant (p=0.355).Conclusion: This research suggests an association between the incident of CTS and longer working period in batik craftsmen.